Sejarah Perkembangan Ekonomi Syariah - Despileny, Iren; Suzana, Suzana; Syahrial, Murah; Syahpawi, Syahpawi (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Islamic economics, as a branch of economic science based on sharia principles. The history of Islamic economics stems from the teachings of Islam which were revealed more than 1400 years ago, with a strong legal basis in the Qur'an and Hadith. Furthermore, during the caliphate period, Islamic economics developed more systematically. The development of Islamic economics stagnated during the colonial period, along with the dominance of the capitalist economic system brought by the colonizers. One of the important milestones in the revival of Islamic economics was the establishment of the Islamic Development Bank (IDB). With a strong historical foundation and continued development, Islamic economics shows its potential as an alternative economic system that is equitable and sustainable. In this research, the method that the author uses is the Historical / Descriptive Method which analyzes the development of Islamic economics from classical to modern times by examining various historical sources and relevant literature. The results of the literature study that have been carried out show that the development of Islamic economics through various periods shows the evolution of economic concepts and practices based on Islamic principles, from the beginning of development to modernization and response to global challenges.